Discovery and biological relevance of 3, 4-didehydroretinol (vitamin A2) in small indigenous fish species and its potential as a dietary source for addressing vitamin A deficiency. (3rd April 2018) - La Frano, Michael R.; Cai, Yimeng; Burri, Betty J.; Thilsted, Shakuntala H.
Abstract: Discovered in the late 1920s, 3, 4-didehydroretinol (DROL, vitamin A2 ) plays a significant biological role in freshwater fish. The functions of this vitamin have been investigated but to a far lesser extent than those of retinol (ROL, vitamin A1 ). A recent study indicating all- trans DROL has 119–127% vitamin A biological activity compared to that of all- trans ROL suggests the significance of DROL for addressing vitamin A deficiency (VAD) in comparison to ROL may be currently overlooked. Freshwater fish such as small indigenous fish species (SIS), with high DROL content can be a promising dietary source for reducing VAD in areas where SIS are readily available and consumed. In this paper, the discovery and biological relevance of DROL are reviewed and furthermore, the vast potential of production and consumption of DROL-rich SIS in food-based strategies to combat VAD in Bangladesh and other developing countries with high prevalence of VAD is highlighted. Graphical Abstract: